The State of the Hepatobiliary System in Children with Obesity and Metabolic Syndrome - Kholmurodovna, Turaeva Dilafruz (American Journal of Biomedicine and Pharmacy, 2025)
Obesity is one of the most important medical and social problems of modern society and is defined as a chronic progressive metabolic disorder with excessive accumulation of adipose tissue and relapses after cessation of treatment. Obesity in children, as a rule, persists into adulthood, leading to severe, life-threatening conditions. First of all, this is type 2 diabetes mellitus and diseases of the cardiovascular system and hepatobiliary system, leading to liver cirrhosis, early disability and premature death.